British foreign secretaries in an uncertain world, 1919-1939 - Hughes, Michael, 1961- (Cass series--British foreign and colonial policy., 2006)
This book examines the careers of the men who served as British foreign secretary between 1919 and 1939, focusing in particular on the ways in which they sought to mould foreign policy.